Biomass bale stack and field outlet locations assessment for efficient infield logistics. (August 2016) - Igathinathane, C.; Tumuluru, J.S.; Keshwani, D.; Schmer, M.; Archer, D.; Liebig, M.; Halvorson, J.; Hendrickson, J.; Kronberg, S.
Abstract: Harvested hay or biomass are traditionally baled for better handling and they are transported to the outlet for final utilization. For better management of bale logistics, producers often aggregate bales into stacks so that bale-hauling equipment can haul multiple bales for improved efficiency. Objectives of this research include simulation of bale collection logistics after forming subfield stacks, evaluation of location effects of bale stack and field outlet, the number of stacks, transported bales/trip, and other field parameters on logistics distances (aggregation, transportation, and total). The software 'R' performed the simulation, statistical analysis, and data visualization. Formation of bale stacks decoupled aggregation and transportation components. Stacks formation thus allows for aggregation and transportation to be performed at different times. Increasing the number of subfield stacks and the number of transported bales/trip significantly reduced the total logistics distances. The order for the best bale stack and outlet locations was: middle, near middle, mid-edge along the length, mid-edge along the width, and finally, corners. Except for swath and windrow variation, the studied field variables had a highly significant influence on the logistics distances. Increased bales/trip (≥6) reduced the variations of outlet locations. Locating the field outlet at or near the center of the field along with an appropriate number of square subfields with stacks at the middle, and increased bales/trip will be the most efficient infield logistics strategy. Graphical abstract: Highlights: Forming bales into subfield stacks decouples aggregation and transportation. Increased subfield stacks and transported bales/trip make efficient logistics. Bale stack and field outlet ranking: middle, mid-edge length, mid-edge width, and corner. Except swath and windrow variation, field parameters significantly affected the logistics. Stacks at subfield middle and outlet at a corner with ≥6 bales/trip is a practical solution.